The role of the teacher: function, missions and timeless purposes - Morgado, Elsa Maria Gabriel (2024)
Objective: The aim of this study is to reflect on the profile and challenges of the teaching profession in a technologically and humanly challenging educational context, with the aim of understanding the relevance and status of the teaching career, as well as assessing and contextualizing the appeal and social commitment of this profession. Theoretical Framework: We brought together leading theorists, methodologists, pedagogues and thinkers related to the world of education and pedagogy, with special emphasis on Portuguese-Brazilian, European and Spanish-American authors. Method: Narrative literature review, seeking to describe or discuss the current state of the research topic. Results and Discussion: The relational triad between the function, the missions and the designs of the teaching function throughout the ages, whose conceptual-reflexive intersection embraces, exposes difficulties and, essentially, points to paths to be trodden in the future by those who (still) respond to the call to embrace a sick career. Implications of the research: In the future, there are certain considerations that can be reflected on and improved, based on the structure and conceptual basis emanating from the reference authors (and works) that deal with the subject under debate and reflection. Originality/Value: This review uniquely promotes reflection on the past (more or less recent) and the present and, above all, identifies some issues to be worked on for the future in this context and in the face of the real and current challenges of the teaching profession, in a socio-economic and socio-political context that is constantly changing, which is largely based on the assumption of the conjectural function of technical-technological conciliation with the interaction and social responsibility of the teacher towards society.